2014
DOI: 10.1371/journal.pone.0102285
|View full text |Cite
|
Sign up to set email alerts
|

Serum Diamine Oxidase as a Hemorrhagic Shock Biomarker in a Rabbit Model

Abstract: BackgroundIn prolonged hemorrhagic shock, reductions in intestinal mucosal blood perfusion lead to mucosal barrier damage and systemic inflammation. Gastrointestinal failure in critically ill patients has a poor prognosis, so early assessment of mucosal barrier injury in shock patients is clinically relevant. Unfortunately, there is no serum marker that can accurately assess intestinal ischemia-reperfusion injury.ObjectiveThe aim of this study was to assess if serum diamine oxidase levels can reflect intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Thus, this indicates that serum D-Lactate reflects the integrity and maturity of intestinal mucosa [42]. DAO is one of the DAO catalyzed by deaminases, only exists in the villi of the upper small intestine, and its increasing concentrations indicate increased intestinal epithelial permeability or damage to intestinal barrier function [43,44]. Serum endotoxins concentration and DAO activity were both increased with the DFRB level.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, this indicates that serum D-Lactate reflects the integrity and maturity of intestinal mucosa [42]. DAO is one of the DAO catalyzed by deaminases, only exists in the villi of the upper small intestine, and its increasing concentrations indicate increased intestinal epithelial permeability or damage to intestinal barrier function [43,44]. Serum endotoxins concentration and DAO activity were both increased with the DFRB level.…”
Section: Discussionmentioning
confidence: 97%
“…The results suggest that there was an increased intestinal permeability in these CRC patients. DAO is an enzyme mainly produced in the small intestine involved in the histamine metabolism [51]. Yee et al has found that an established first-line treatment for patients in T2DM, metformin, inhibits DAO activity [52].…”
Section: Discussionmentioning
confidence: 99%
“…The DAO is a key marker for monitoring intestinal barrier permeability (33) . When the intestinal mucosal barrier integrity is injured, intestinal DAO will release into the circulation and plasma DAO activity increased (34) . In the present study, plasma DAO activity was significantly increased after piglets being challenged by E. coli K88, indicating that intestinal barrier function was attainted, which was consistent with previous study (35) .…”
Section: Discussionmentioning
confidence: 99%